Penggunaan Keran Air Otomatis dalam Penghematan Air - Antonius Rildo Pramudya; Alfeto Alfeto; Chaterine Cristianti (Ultima Computing : Jurnal Sistem Komputer, 2020)
Water is an important source for human life. Nowadays, clean water has begun to be rare and therefore it is necessary to conserve water. In this study we made an automatic water faucet to fill the container. The use of this automatic tap aims to stop the water flow when the filled container reaches the desired height. The tools used are Arduino uno, ultrasonic sensors, solenoid valves, and potentials. Before use the appliance must be calibrated first before being used daily. However, in an automatic water faucet experiment it will only stop based on the height set by us. Index Terms : Water faucet, ultrasonic sensor, arduino uno, solenoid valve.